Development and validation of a survey questionnaire assessing technological pedagogical content knowledge and E-learning acceptance for Malaysian English teachers - Lim, Pei Sing; Wardatul Akmam Din; Nik Zaitun Nik Mohamed; Suyansah Swanto (Global Academic Excellence, 2022)
The traditional method of teaching and learning is found to fail in developing English language as a skill among the learners. E-learning is stated as a powerful tool for educational change and reform to improve English language teaching and learning. The implementation of e-learning in education has shown significant growth over the last decade with the rapid development of technology. The emergence of the Covid-19 pandemic around the world in 2019 has risen the implementation of e-learning as an alternative way of teaching and learning. The major challenges faced by teachers in implementing e-learning involve issues such as low Technological Pedagogical Content Knowledge (TPACK) level and technology acceptance. In line with this, this study aims to develop and validate an instrument to measure TPACK and e-learning acceptance, particularly for English teachers in Malaysia. This survey produced an adapted survey questionnaire that combines TPACK for English teachers’ questionnaire items and perceived ease of use and perceived usefulness questionnaire items. The content validity and face validity of the developed survey questionnaire were identified using CVI and FVI calculations. The experts and raters pointed out that all items are relevant and comprehensible. Some minor improvements can be done based on the suggestions given. The results of CVI (0.89) and FVI (0.94) show that the developed survey questionnaire is found to achieve a satisfactory level of both content validity and face validity and can be used for further study.